1991
DOI: 10.1182/blood.v78.3.703.bloodjournal783703
|View full text |Cite
|
Sign up to set email alerts
|

Expression of interleukin-4 receptors on early human B-lineage cells

Abstract: Interleukin-4 (IL-4) regulates multiple stages of the antigen-dependent phase of B-cell development. However, its precise role in regulating B lymphopoiesis in bone marrow is not as well defined. We examined whether surface IgM- normal and leukemic human B-cell precursors (BCP) expressed IL-4 receptors using biotinylated IL-4. Constitutive expression of IL-4 receptors was detected on both normal and leukemic BCP. A higher percentage of normal BCP (82% +/- 15%) expressed IL-4 receptors compared with leukemic BC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
1

Year Published

1992
1992
1997
1997

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 0 publications
0
3
1
Order By: Relevance
“…The high SSC population expressed high levels of cell surface CD23, a broadly distributed 45-kD glycoprotein (33). CD23 has been described to represent a stagespecific marker on slgM + B cells before isotype switching in B cell ontogeny (34,35). The present data, however, demonstrate that CD23 is inducible before acquisition of slgM.…”
Section: Discussioncontrasting
confidence: 54%
See 1 more Smart Citation
“…The high SSC population expressed high levels of cell surface CD23, a broadly distributed 45-kD glycoprotein (33). CD23 has been described to represent a stagespecific marker on slgM + B cells before isotype switching in B cell ontogeny (34,35). The present data, however, demonstrate that CD23 is inducible before acquisition of slgM.…”
Section: Discussioncontrasting
confidence: 54%
“…In parallel to our results on BCP, it is of interest that mature B cells have recently been reported to acquire CD23 upon culture in the CD40 system (36). Unlike its effect on mature B cells (37), IL-4 does not appear able to promote CD23 expression on BCP (35) (our unpublished data). Thus, CD40-mediated induction of CD23 on BCP could be independent of IL-4.…”
Section: Discussionmentioning
confidence: 80%
“…We examined IL-4 because it is the most effective cytokine for culturing mature B cells in the 'CD40 system'. Besides, IL-4 receptors are expressed on leukaemic B-cell precursors (Law et al, 1991), although IL-4 was also reported to be toxic for leukaemic B-cell precursors (Okabe et al, 1991;Manabe et al, 1994). Indeed, we found a clear suppressive effect of IL-4 on the growth of ALL cells.…”
Section: Time Curvesmentioning
confidence: 50%
“…Indeed CLL is due to the malignant proliferation of B cells that are arrested ("frozen") at a discrete stage of their maturation. Finally, it is of note that malignant pre-B cells, from patients with acute lymphoblastic leukemia, may be induced to express CD23 following stimulation with IL-4 (Law et al, 1991).…”
Section: Cellular Distributionmentioning
confidence: 99%